KETERBUKAAN ORGANISASI : TANGTANGAN DALAM MENGHADAPI PERSAINGAN - Rullijanto DP (Media Riset Bisnis & Manajemen, 2001)
The competition that happens these days not only limited to competition among national companies but also against foreign companies, the competition Affect Company's wills behavior.  Competition creates, uncertainty, without a high a company may face a big problem in this new global arena quality of human resources.